VizieR Online Data Catalog: V1162 Ori variations (Arentoft+, 2001) - Arentoft, T.; Sterken, C.; Handler, G.; Freyhammer, L. M.; Bruch, A.; Niarchos, P.; Gazeas, K.; Manimanis, V.; van Cauteren, P.; Poretti, E.; Dawson, D. W.; Liu, Z. L.; et al. (VizieR Online Data Catalog, 2001)
V1162 Ori is a delta Scuti star with variable period and amplitude. To analyse data acquired in the years 1998-2000, the data were subdivided in smaller subsets to take the amplitude and period variability into account. Four different ways of subdividing the data discussed in the paper are outlined in this table 2. A database containing the observations of V1162 Ori is in preparation; it will be published in the Journal of Astronomical data (http://www.vub.ac.be/STER/JAD/jad.htm). (2 data files).
Keywords: Stars: variable